A Study of Islamic Values in School Learning - Fitriani; Dasrieny Pratiwi; Arif Rahman Aththibby; Friska Octavia Rosa (Yayasan Payungi Smart Madani, 2025)
This study aims to examine the process of internalizing Islamic values in school learning as a strategy for holistically shaping students' character. The study focuses on three fundamental values of Islamic education: faith, sharia, and morals, understood as a unified, interrelated value system. This research employed a qualitative approach using literature review methods, including relevant national and international peer-reviewed scientific articles. Data were analyzed inductively through the stages of comparing, critiquing, and synthesizing previous research findings. The results indicate that internalizing the values of faith, sharia, and morals contributes significantly to the formation of students' religious, social, and moral character. The internalization process occurs through three main stages: understanding, habituation, and practice, reinforced by teacher role models, a religious school culture, and synergy between the school and family. The integration of Islamic values not only enhances cognitive religious understanding but also shapes students' attitudes and behaviors in their daily lives. Overall, this study confirms that the integration of Islamic faith, sharia, and moral values in learning constitutes a strategic and sustainable approach to character education and provides conceptual and practical contributions as a foundation for developing Islamic values-based learning models relevant to national education policies and the challenges of modern education.